A Production and Operations management study on Kisses Fruit Juice and Ice Candy Company - Arceo, Ethel (College of Engineering, 2001)
Kisses Fruit Juice and Ice Candy Company, a small scale industry, started its operations in 1989. The fruit juices that the company manufactures come in two sizes, the 192 ml Regular size and the 110 ml Junior size. Flavors for the fruit juices are apple, pineapple, orange, grape and strawberry. The same flavors are used in making the 50 ml ice candies. However, instead of apple, guyabano flavor is used. Customers are limited to Bulacan area and includes dealers and public markets. Raw materials are all bought from suppliers in Bulacan and Metro Manila. The whole production process is done in the shop floor, from the melting of the sugar to the packing of the final products. No process is outsourced. The study aims to analyze the production system that the company currently employs and identify the problems that may hinder the company?s growth. a thorough documentation of the company?s organizational structure, layout, capacity, inventory system and production processes was done. Key personnel were interviewed in order to gain more knowledge about the company?s operations. Through the use of Streamline Diagnosis Diagram, different problems in the company and their potential causes were identified. The main problems are unbalanced production line, absence of definite production schedule, and the absence of a forecasting method. Through analysis of these problems, it is recommended that 11 out of the 30 sealers be sold and of the remaining 19, 11 be rented out. An excess number of sealers must be kept in the vent that demand may peak again to the level that the company experienced before. A production schedule was also created to facilitate a much orderly production as well as to ensure the freshness of the products being delivered to the customers. For forecasting, it is suggested that an exponential smoothing method with trend effects be used by the company. By using the aforementioned forecasting method, the company may predict demand for the next year based on the current year?s demand and then set its resources and production accordingly. These recommendations aim to provide the company with a more efficient production system. It is expected that through the flow of the production process will be smoother and more orderly. IF a suitable forecasting method is employed, the company will have a more reliable basis for production schedule and they will be able to easily adjust production in order to cope up with changes in demand because of trend effects and other factors.